Modelling trust in customer and supplier interaction: a simulation of dynamic performances - Gan, Chun Chet (UiTM Cawangan Johor, 2023)
This paper writes about a theoretical model developed to understand trust in customer and supplier relationship. The model developed considers seven variables in an interaction between a customer and a supplier. These influencing factors suggest here affect customer 's trust towards their suppliers. These factors are (1) Control, (2) Feedback, (3) Delay, (4) Disturbance, (5) Co-operation, (6) Supplier 's Commitment and (7) Distance. The model proposes that a supplier 's performance in a high volume with repeated transactions environment is dynamic. It is written here that making decision (investment) based on past supplier 's repeated performances are possible links to trust. Simulation of supplier dynamic performance proofs the links possible, making prediction possible of what is known.